Dinamika Pendidikan Islam di Indonesia pada Era Orde Baru: Tantangan dan Peluang - Dewi Masruroh; Moh. Kusno; Moh. Fiqih Firdaus (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
Islamic education during the New Order era (1966–1998) experienced complex dynamics amid ideological pressures and authoritarian, centralized government policies. This study aims to examine the concepts and policies of Islamic education during this period and identify the challenges and opportunities that emerged in its development process. The method used is a literature review, collecting data from relevant scholarly journals, articles, and related literature. The findings show that although Islamic education faced ideological repression due to the mandatory P4 indoctrination and political doctrines, significant opportunities arose, such as the recognition of madrasahs as equal to public schools, compulsory Islamic religious lessons at all education levels, and the establishment of strategic institutions like the Indonesian Ulama Council and Bank Muamalat Indonesia. Major challenges included a centralized education system, restrictions on academic freedom, and cultural homogenization, which hindered the development of progressive Islamic education. In conclusion, Islamic education during the New Order experienced transformations that shaped the direction and identity of Islamic educational institutions in Indonesia. These findings are important for formulating more inclusive and adaptive strategies for the future development of Islamic education.